Association of trace elements with lipid profiles and glycaemic control in patients with type 1 diabetes mellitus in northern Sardinia, Italy: An observational study. (August 2015) - Peruzzu, Angela; Solinas, Giuliana; Asara, Yolande; Forte, Giovanni; Bocca, Beatrice; Tolu, Francesco; Malaguarnera, Lucia; Montella, Andrea; Madeddu, Roberto
Highlights: The blood Zn level influences the distribution of TG, TC, and LDL. Cu and Cr are more strongly associated with glycaemic control. Se was significantly and positively correlated with triglycerides. Zn, Fe, and Se are more strongly associated with lipid metabolism. Abstract: Sardinia is an Italian region with a high incidence of type 1 diabetes mellitus. This study aimed to determine the associations of trace elements with lipid profiles and glycaemic control in patients with T1DM. A total of 192 patients with T1DM who attended the Unit of Diabetology and Metabolic Diseases in Sassari, Italy, were enrolled. Trace elements zinc, copper, selenium, chromium, and iron were measured in whole blood by sector field inductively coupled plasma mass spectrometry. The correlations between metabolic variables and the levels of trace elements were determined. Zinc was positively correlated with total cholesterol ( P  = 0.023), low-density lipoprotein ( P  = 0.0015), and triglycerides ( P  = 0.027). Iron as significantly correlated with TC ( P  = 0.0189), LDL ( P  = 0.0121), and high-density lipoprotein (HDL) ( P  = 0.0466). In males, Cr was positively correlated with HDL ( P  = 0.0079) and Se, in females was correlated with TG ( P  = 0.0113). The mean fasting plasma glucose was166.2 mg dL −1 . Chromium was correlated with fasting plasma glucose ( P  = 0.0149), particularly in males ( P  = 0.0038). Overall, 63.5% of the patients had moderate HbA1c (7–9%). Copper was significantly correlated with HbA1c% in males ( P  = 0.0155). In conclusion, the results of this study indicate that trace elements show different associations with lipid levels and glycaemic control in T1DM. Zinc, Fe, and Se were associated with lipid levels whereas Cu and Cr were associated with HbA1c%.